1: Fat Grafting Improves Dorsal Skin Fibrosis after Radiation in an Engrailed-1 Mouse Model. (July 2021) - Abbas, Darren B.; Fahy, Evan J.; Lavin, Christopher; Griffin, Michelle; Adem, Sandeep; Diaz Deleon, Nestor M.; Mascharak, Shamik; King, Megan; Lee, Daniel; Longaker, Michael T.; Wan, Derrick C.
Abstract : Purpose: Fat grafting is known to rejuvenate and improve fibrosis in irradiated skin, but the underlying mechanisms behind these effects are poorly understood. We have previously identified the Engrailed-1 fibroblast sub-population as having a role in post-natal dorsal skin fibrosis in mice. Using a radiation model to the scalp of Engrailed-1 mice, we sought to better understand the regenerative effects of fat grafting in irradiated tissue. Methods: Adult (60-day old) En1 Cre ;R26 mTmG transgenic mice (n=5) underwent total body irradiation with 9 Gy for immunodepletion. Mice were then immediately reconstituted with 2 million nucleated bone marrow cells from donor NSG(NOD.CB17- Prkdcs scid /J) mice via retro-orbital injections. Reconstitution was confirmed with fluorescence-activated cell sorting (FACS) 2 weeks after whole body irradiation. Mice scalps were then irradiated with 5 Gy every other day for 12 days (30 Gy total) and allowed to recover for 4 weeks to facilitate fibrotic conversion. Irradiated scalps were grafted with 200μL of fresh human lipoaspirate. Graph retention was measured in-vivo for 8 weeks using Micro-Computed Tomography Scanner (Bruker SkyScan 1726 ™ ) and scalp skin was harvest for histology. Results: Two weeks post bone-marrow transplant, >90% of circulating hematopoietic cells (CD45 + ) cells in En1 Cre ;R26 mTmG reporter mice were non-fluorescent, signifying successful reconstitution. Volumetric analysis of fat grafting in-vivo was performed using 3-dimensional reconstruction. At 8 weeks post-grafting, 4 of the 5 grafts demonstrated >50% graft retention, confirming successful grafting. Histological sections of scalp skin 8 weeks post-grafting demonstrated significantly less En1+ GFP cells compared to non-grafted scalp skin, signifying less presence of En1 + fibroblasts. Furthermore, histology demonstrated significantly less dermal thickening, epidermal thinning, and collagen deposition and disorganization in fat grafted irradiated scalp skin compared to non-grafted scalp skin. Conclusion: Fat grafting mitigates radiation-induced fibrosis in scalp skin by decreasing collagen deposition, remodeling collagen formation, decreasing epidermal thinning, and reducing presence of pro-fibrotic fibroblast sub-populations.